Apocalypses and the Sage. Different Endings of the World in SenecaApocalypses and the Sage. Different Endings of the World in Seneca - Romana Berno, Francesca (Gerión. Revista de Historia Antigua, 2019)
This paper deals with apocalypse, intended as a revelation or prediction related to the end of the world, in Seneca’s prose work. The descriptions and readings of this event appear to be quite different from each other. My analysis will follow two main directions. Firstly, I will show the human side of the question, focussing on the condition of the sage facing the universal ruin in the context of the macroscopic narrative structure of most passages, and on the differences between the Epicurean and the Stoic view on this point. Secondly, I will turn to the descriptions of the end of the world which we can find in the Naturales Quaestiones. I will argue that Seneca’s choice of flood or conflagration as representations for the apocalypse are not haphazard, but may be motivated by a subtle political narrative, and thus linked to the Stoic struggle for taking part in the governing of the state. In particular, the end of book three represents a flood which probably alludes to Tiber’s floods.